The run of ourselves: Shame, guilt and confession in post-Celtic Tiger Irish media. (May 2018) - Free, Marcus; Scully, Clare
This article examines the emergence of the themes of shame and guilt in Irish print and broadcast media in the wake of Ireland's 2008 economic collapse. It considers how the potential search for explanation of the crisis as a manifestation of unregulated banking and development sectors was displaced onto a confessional discursive pattern in which emphasis was placed on rampant borrowing and consumption as reflective of collective narcissism and acquisitive greed. Hence the logic that 'hubris' led inevitably to a national fall from grace and the corresponding resurgence of postcolonial shame; and the interplay between cultural nationalist and neoliberal discourses of redemption through confession of guilt and disciplinary self-regulation as the purging of excess.